Regional Government Strategy in Improving Tourism Management to Increase Community Income in Namalatu Beach and Latuhalat Village Leisure Beach - Kenny Harold Terinathe; Erly Leiwakabessy; Jopie Tamtelahitu (LP2M IAIN Palopo, 2026)
This study aims to analyze the local government's strategy in improving tourism management to increase community income in Namalatu Beach and Latuhalat Village Leisure Beach. Research problems include low community capacity to take advantage of tourism economic opportunities, limited supporting facilities, lack of optimal coordination between the government and the community, and weak tourism promotion. The research uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The research informants consisted of the village government, the Tourism Office, tourism managers, and local business actors. The results of the study show that local government strategies have been carried out through facility development, community empowerment, and regulatory support, but they have not run optimally due to limited training, uneven community participation, and not yet optimal digital marketing. The concept of Community-Based Tourism has not been applied comprehensively so that the economic impact on the community is still fluctuating and depends on the tourist visit season. The conclusion of the study shows that strengthening government and community collaboration, increasing human resource capacity, developing digital promotions, and sustainable tourism management are key factors in increasing community income. It is suggested that local governments improve training programs, improve tourism facilities, and build an integrated community-based management system